Whole exome sequencing identification of novel candidate genes in patients with proliferative diabetic retinopathy. (October 2017) - Ung, Cindy; Sanchez, Angie V.; Shen, Lishuang; Davoudi, Samaneh; Ahmadi, Tina; Navarro-Gomez, Daniel; Chen, Ching J.; Hancock, Heather; Penman, Alan; Hoadley, Suzanne; Consugar, Mark; Restrepo, Carlos; et al.
Abstract: Rare or novel gene variants in patients with proliferative diabetic retinopathy may contribute to disease development. We performed whole exome sequencing (WES) on patients at the phenotypic extremes of diabetic retinal complications: 57 patients diagnosed with proliferative diabetic retinopathy (PDR) as cases and 13 patients with no diabetic retinopathy despite at least 10 years of type 2 diabetes as controls. Thirty-one out of the 57 cases and all 13 controls were from the African American Proliferative Diabetic Retinopathy Study (AA). The rest of the cases were of mixed ethnicities (ME). WES identified 721 candidate genes with rare or novel non-synonymous variants found in at least one case with PDR and not present in any controls. After filtering for genes with null alleles in greater than two cases, 28 candidate genes were identified in our ME cases and 16 genes were identified in our AA cases. Our analysis showed rare and novel variants within these genes that could contribute to the development of PDR, including rare non-synonymous variants in FAM132A, SLC5A9, ZNF600, and TMEM217 . We also found previously unidentified variants in VEGFB and APOB . We found that VEGFB, VPS13B, PHF21A, NAT1, ZNF600, PKHD1L1 expression was reduced in human retinal endothelial cells (HRECs) cultured under high glucose conditions. In an exome sequence analysis of patients with PDR, we identified variants in genes that could contribute to pathogenesis. Six of these genes were further validated and found to have reduced expression in HRECs under high glucose conditions, suggestive of an important role in the development of PDR.